The Extent of Inclusive Design from Indonesian Architects’ Perspective - Ula, Zuhrotul Mawaddatil; Andracana, I Gusti Ngurah; Hayati, Arina; Cahyadini, Sarah (MAJ - Malaysia Architectural Journal, 2025)
The importance of inclusive design, acknowledged in SDGs 10 and 11, aims to ensure leaving no one behind in developing and improving the built environment. However, in reality, especially in developing countries, the built environments often fail of adequately accommodating those with special needs. Some studies highlighted the missing link between research and discussions about inclusive design and its implementation within the built environment. Given architects' pivotal role in shaping the built environment, it becomes imperative to investigate their perspectives on inclusive design throughout the design process and in the final product. This research provides a preliminary study exploring the concept of inclusive design through the lens of Indonesian architects. Involving questionnaires as the primary tool for data collection, this research assesses the comprehension of inclusive design, their application in the design process, and the level of user involvement as an important part of inclusive design. Secondary sources such as previous research, reports, and news articles were utilized to contextualize the discourse surrounding inclusive design in Indonesia. The collected data were analyzed using quantitative data coding, which is weighted in the sum of the frequency of occurrence based on the mentioned aspects of assessment. The findings reveal that most Indonesian architects are aware of, understand, and apply inclusive design in their architectural practices. However, they tend to focus on physical rather than equally accommodate physical and psychological matters. They have involved users in their design process, although their consistency needs to be enhanced. The challenge they face in utilizing this concept needs to be positioned as an asset. Then, while Indonesian architects recognize the importance of inclusive design, deeper comprehension and integration into the design process still need to be further developed.